Main Directions and Tools of the Information and Analytical Culture of the Modern Manager of Library Socio-Cultural Activities in Ukraine: a Competent Approach - Okhrimenko Hanna (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The study presents a description of the roles of the manager of library socio-cultural activities in Ukraine through the prism of the competence approach. Manager is a specialist who possesses pronounced leadership qualities and the qualities of an entrepreneur, who is able to learn and develop constantly. The main manageri’ roles are: inter personal roles (this is a link connecting with external organizations and individuals); informational roles (receiver and disseminator of information (internal and external); roles related to decision-making (liquidator of violations in the organization’s activities and disseminator of resources). The basic feature of management in the field of culture is that the provision of resources is based on the involvement of the interests of various social institutions: sponsors, investors, charitable organizations, and other donors. A modern cultural manager has to perform his/her role, depending on his/her position in the hierarchical pyramid, by making strategic, managerial or operational decisions. At the same time, it is necessary to possess analytical and communication skills for establishing communication with employees and the public, as well as receiving and transmitting information data for the systematic functioning of the organization. In this context, it is worth highlighting the main directions of the information and ana lytical culture of the manager of socio-cultural activities: 1) Information hygiene and media literacy of the manager of socio-cultural activities; 2) Visualization of the ideas of the manager of socio-cultural activities; 3) Preparation of storytelling presentations as a high-quality information and analytical product; 4) Formation of corporate culture and management decision-making based on qualitative data.